A healthy lifestyle is the base of maintaining the health of schoolchildren - G.V. Beketova; K.B. Savinova; G.P. Mozgova; N.V. Beketova (Zdorovʹe Rebenka, 2021)
Background. A healthy lifestyle is an active motion of people aimed at maintaining and promoting health, as conditions and preconditions for the implementation of other aspects of life aimed at overcoming the causes and progression of diseases, using social and natural conditions to protect and improve health. The main components of a healthy lifestyle include sufficient physical activity according to age, optimal nutrition, sufficient physical activity, healthy and adequate sleep, the absence of bad habits. It is important to form an idea of a healthy lifestyle since childhood. And in this regard, a very interesting and effective experience is the introduction of health technologies (HST) in the work of preschool and school educational institutions. HST is the construction of a sequence of factors that prevent the destruction of health while creating a system of favorable conditions for its preservation. The study was aimed to estimate the impact of the author’s health-saving technology “Education in Moving” by Professor O.D. Dubogai on the formation of skills for a healthy lifestyle among primary school students. Materials and methods. A comprehensive clinical and instrumental examination of 153 children before entering school and during grades 1–4 was conducted at the Kyiv Regional Children’s Hospital in Boyarka. Among them, 65 students of secondary school (SS) No. 287 in Kyiv, where HST “Education in Moving” of Professor O.D. Dubogai was implemented — I (basic) group, and 88 students of school No. 3 in Boyarka, Kyiv region, who studied by the generally accepted methods — group II (control). Results. In group I, there was a significant increase in the number of children with harmonious physical development (from 27.7 to 63.9 %), and there were no changes in the control group (38.6 % in class I and 41.7 % in class V); the number of students with satisfactory adaptive-reserve capabilities of the cardiovascular system (CVS) increased on the Baevsky index (97.2 and 33.3 %); 77.6 and 8.4 % of pupils, respectively, had a high level of cardiac functional reserve (Rufier’s test). Functional reserves of the respiratory system increased (from 41.5 to 88.9 %), and in controls, it reduced by half. The number of students with satisfactory results on the breath-holding test increased from 67 to 87%, and in the controls, it decreased by 2.7 times. At the end of primary school, the Genche’s test was satisfactorily performed by 100.0 % of children in group I, and in group II by 76.5 %. In group I, the number of children with a high life index increased significantly (from 58.5 to 97.2%), and in the control group, this indicator decreased from 27.3 to 16.7 %. The anti-infectious resistance in group I students has improved: in grade 4, the number of missed days of study per year per student was 15.9, and in the controls — 53.9 days; the percentage of recurrent respiratory infections decreased from 5.0 to 2.5 % against 7.5 % in the control group, and their complicated forms (from 15.0 to 3.5 % vs 16.0 %), while in group I, the frequency of chronic pathology didn’t increase and CVS dysfunction decreased. Having implemented the HST ”Education in Moving” system in the basic group proved increasing of the amount of the children with harmonic physical fitness in 36.6 %, and changes in the physical fitness among children of the control group were slightly observed (from 38.6 to 41.7 % at the grade 4). The indices of the functional state of the CVS improved under the influence of the HST, the number of children with satisfying adaptive-reserved abilities by the Baevski’s index positively grew (97.2 against 33.3 % in the group of control after graduation from the primary school). 77.6 % of the children in the basic group had the high and above the average level of the heart functional reserve (by the data of the Ruffier test) and only 8.4 % of the children in the control group had the same result. Also, the functional reserve of the respiratory system grew in the children of the basic group: while using the HST, the amount of the children with satisfying results of the breath-holding test increased from 67.0 to 87.0 %, and in the control group, its values decreased from 62.5 to 24.5 %. Hench’s test was done successfully by 100 % of children in the basic group at the end of the academic year, while in the control group, only 76.5 % of children performed it. The communicable resistance improved in children of the basic group: the amount of missed days in the year by one pupil was 15.9, while in the control group was 53.9 days. The quantity of the children with chronic pathology didn’t increase in the basic group, the proportion of students with functional disorders of the cardiovascular system positively reduced from 30.8 to 8.3 %. Conclusions. Thus, our research has proved the positive impact of the HST “Education in Moving” system on the formation of skills of a healthy lifestyle among children of primary school age, showed its effectiveness in maintaining the health of primary school children, which allows us to recommend above-mentioned HST for the wide implementation in comprehensive schools.